Disappearing war : interdisciplinary perspectives on cinema and erasure in the post-9/11 world - Hellmich, Christina, 1978-; Purse, Lisa (Edinburgh University Press Ltd, 2017)
The battles fought in the name of the ́⁰war on terroŕ⁰₉ have re-ignited questions about the changing nature of war, and the experience of war for those geographically distant from its real world consequences. What is missing from our highly mediated experience of war? What are the intentional and unintentional processes of erasure through which the distortion happens? What are their consequences? Cinema is a key site at which questions about our highly mediated experience of war can be addressed or, more significantly, elided. Looking at a range of films that have provoked debate, from award-winning features like Zero Dark Thirty and American Sniper, to documentaries like Kill List and Dirty Wars, as well as at the work of visual artists like Harun Farocki and Omer Fast, this book examines the practices of erasure in the cinematic representation of recent military interventions. Drawing on representations of war-related death, dying and bodily damage, this provocative collection addresses ́⁰what́⁰₉s missinǵ⁰₉ in existing scholarly responses to modern warfare; in film studies, as well as in politics and international relations.
Keywords: War films -- History and criticism.; Films de guerre -- Histoire et critique.; PERFORMING ARTS -- Reference.; PERFORMING ARTS -- Film & Video -- History & Criticism.; War films; Elfter September; Kriegsfilm; Dokumentarfilm; Krieg -- Motiv; Criticism, interpretation, etc.